2000
DOI: 10.1029/1999jd900926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of daily UV doses estimated from Nimbus 7/TOMS measurements and ground‐based spectroradiometric data

Abstract: Abstract. During recent years, methods have been developed for estimating UV irradiance reaching the Earth's surface using satellite-measured backscattered UV radiances. The NASA-developed method is based on radiative transfer calculations and satellite measurements of parameters affecting UV radiation: extraterrestrial solar irradiance, atmospheric ozone, cloud reflectivity, aerosol amounts, and ground albedo. In this work a comparison is made between daily UV erythemal doses estimated from Nimbus-7/TOMS meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 25 publications
8
78
2
1
Order By: Relevance
“…Satellite ozone and UV data were exhaustively validated by means of GB measurements, regarding TOMS; (Kalliskota et al, 2000;McKenzie et al, 2001;Krotkov et al, 2001;Fioletov et al, 2002;Meloni et al, 2005;Arola et al, 2005;Kazantzidis et al, 2006) and lately OMI; Ialongo et al, 2008;Weihs et al, 2008;Kazadzis et al, 2009;Buchard et al, 2008). All these validation studies converge to the following conclusions:…”
Section: S Kazadzis Et Al: Omi Sub-pixel Uv Irradiance and Aerosol mentioning
confidence: 86%
“…Satellite ozone and UV data were exhaustively validated by means of GB measurements, regarding TOMS; (Kalliskota et al, 2000;McKenzie et al, 2001;Krotkov et al, 2001;Fioletov et al, 2002;Meloni et al, 2005;Arola et al, 2005;Kazantzidis et al, 2006) and lately OMI; Ialongo et al, 2008;Weihs et al, 2008;Kazadzis et al, 2009;Buchard et al, 2008). All these validation studies converge to the following conclusions:…”
Section: S Kazadzis Et Al: Omi Sub-pixel Uv Irradiance and Aerosol mentioning
confidence: 86%
“…In that work, the OMI Lambertian Equivalent Reflectivity (LER) at 360 nm was used to describe cloud-free conditions. A certain day was classified as cloudfree if LER was lower than 10% (Kalliskota et al, 2000). Thus, 703 (49% of the total days) days were selected as cloud-free.…”
Section: Site Instruments and Datamentioning
confidence: 99%
“…Clouds often mask the influence of total ozone on UV radiation and may cancel, reduce or enhance the expected UV signal (e.g., Schafer et al, 1996;Sabburg et al, 2003;Calbo et al, 2005). In addition to total ozone and clouds, ground albedo is another significant factor influencing UV radiation, with snow cover and depth being the largest factors affecting the albedo (e.g., Blumthaler and Ambach, 1988;McKenzie et al, 1998;Weihs et al, 1999Weihs et al, , 2001Schmucki and Philipona, 2002), with snow albedo being highly dependent on age and type of snow (e.g., Vanicek et al, 2000;Kalliskota et al, 2000). Moreover, several studies have shown that high surface albedo can lead to an enhancement of UV radiation by up to 70 % or more, with the highest enhancements observed during partly cloudy conditions (e.g., McKenzie et al, 1998;Simic et al, 2011).…”
Section: P Weihs Et Al: the Influence Of The Spatial Resolution Of mentioning
confidence: 99%